A conversation with Emeritus Professor Frank Stilwell, Department of Political Economy, University of Sydney. (1st January 2014) - Thornton, Tim
This discussion, with a true pioneer of pluralist economics teaching, examines a particular strategy for achieving reform that has been adopted at Sydney University. It is a strategy that may have wide applicability for the reform of economics. The strategy is shown to have two features. Firstly, there has been the pursuit of institutional independence: a separate department of pluralist economics has been established that is independent of the existing neoclassical economics department. The second feature of the strategy has been one of explicit disciplinary differentiation: a pluralist economics is taught using the disciplinary title of 'political economy' rather than 'economics'. The discussion also offers a range of interesting insights on the mainstream research frontier, the relationship between a pluralist economics and other social sciences, and the issues facing mainstream economists.